Active, experiential and reflective training in civil engineering: evaluation of a project-based learning proposal. (1st November 2020) - Miranda, Marina; Saiz-Linares, Ángela; da Costa, Almudena; Castro, Jorge
ABSTRACT: In today's industry, employers are looking for civil engineering graduates who have acquired not only substantial technical and scientific knowledge, but who also have good life-long learning skills such as problem-solving, creativity and communication skills. Therefore, it is necessary to leave behind the pedagogical approaches exclusively sustained in master classes in favour of active, experiential and reflective curricula. Thus, a Project-Based Learning (PjBL) strategy has been developed as part of two geotechnical courses within a civil engineering degree in Spain to promote these skills. A qualitative analysis of the implemented PjBL strategy is performed by means of questionnaires and interviews with the aim of considering the participants' perceptions. The results of the analysis are presented under the following headings: benefits and difficulties of the PjBL, teacher role, traditional teaching methods and measures of improvement. The results suggest a satisfactory implementation, and they have allowed the authors to share the lessons learned from this experience by generating some 'tips' for future implementations.